KREDIT BARANG DALAM SISTEM PEMBAYARAN PAYLATER DI TRANSAKSI JUAL BELI ONLINE - Cahyono, Rudi; Hasan Basri; Fathul Qorib (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstract The impact of increasing technological progress and the internet seems to have contributed to the Indonesian financial system. One example is seen with the development of financial technology in the community. Fintech or financial technology is the name of an innovation in the field of financial services that iscombined with technology. Fintech is currently gaining popularity with the PayLater feature, aka pay later. The PayLater feature is very popular quickly due to the advancement of payment system technology in giant e-commerce such as Tokopedia, Shopee, Traveloka, Bukalapak, Kredivo, etc. This research is normative legal research. The researcher uses a data collection tool in the form of a literature study by examining OJK Regulation Number 77/POJK.01/2016. The main legal basis used in lending and borrowing activities in fintech activities is POJK 77 of 2016. In the Shopee PayLater service, the standard agreement scheme is used. So, for PayLater users, in activating the payment system, they should understand in advance about the terms and conditions, namely the contents of the agreement set by the e-commerce party and the organizer. from one of the parties on the Shopee PayLater service in the form of an administrative warning. PayLater users are expected to pay bills in accordance with the agreed time in order to avoid these sanctions. Keywords: Credit, PayLater, Buy and Sell Online.